The effects of music intervention on pediatric burn patients during treatment: a systematic review and meta-analysis - Chen, Bin; Qiu, Riti; Huang, Hua (Frontiers in Neurology, 2025)
BackgroundBurns rank among the foremost causes of accidental death and injury in children and pediatric patients, and their treatment poses significant challenges. Music intervention has demonstrated considerable potential in alleviating pain and anxiety in pediatric burn patients during treatment. The present meta-analysis was designed to assess the impact of music intervention on the treatment of pediatric burn patients.MethodsWe conducted a comprehensive search across multiple databases, including PubMed, Web of Science, Embase, and Cochrane Library, to identify studies that met inclusion criteria. Only RCTs published in English that evaluated the efficacy of music intervention in pediatric burn patients were considered eligible for inclusion. The quality assessment of the included studies was performed using the Cochrane risk-of-bias tool. This study was performed based on the Guidelines of Systematic Reporting of Examination presented in the PRISMA checklist. The search protocol has been registered at the PROSPERO International Prospective Register of Systematic Reviews.ResultsFour RCTs met the inclusion criteria, involving 158 pediatric burn patients aged from 1 day to 20 years who received either live music therapy or recorded music. Overall, a statistically significant positive effect was observed on both pain [SMD = −0.43, 95% CI (−0.80, −0.07)] and anxiety [SMD = −0.66, 95% CI (−1.05, −0.28)]. However, the music intervention group did not show a statistically significant reduction in heart rate [SMD: 0.20, 95% CI (−0.49, 0.89)] or respiratory rate [SMD: −0.21, 95% CI (−0.90, 0.47)].ConclusionFindings from this study indicates that Music intervention has a positive effect in alleviating pain and reducing anxiety in children and adolescents with burn injuries.